Pengaruh Motivasi, Disiplin Dan Kompensasi Kerja Terhadap Kinerja Karyawan Pada PT. Pos Indonesia Kantor Pos Wonogiri - Prabowo, Yoga Ammar, Edi Purwo Saputro, S.E., M.Si (2017)
The objective of this study is to determine the influence of motivation, discipline and work compentation towards employee performance in PT. Pos Indonesia, Wonogiri Post Office. The sampling technique used in this study is Confinient Sampling. The data type and source of data used in this study is primary data which is collected from the respondents who have filledin the questionnaire. Data analysis techniques used that is the best of validity with all the variables declared invalid value corrected item-total correlaticon of each variable above 0,254, with realibility test result singer research testing each variable is declared reliable with Cronbach Alpha above 0,600. By criteria that employee performancewell as variable motivation, discipline and work compentation on employee performance, hypothesis testing through t test motivation, discipline and work compentation significant. Test F on each of thevariables significantly and influence operates commercial test article R2 of 69,1% and the rest of her is explained by variables lie at 30,9%. It can be concluded that the employess of PT. Pos Indonesia, Wonogiri Post Office need motivation, discipline and work compentation to improve their work performance in order to reach the company's goals and objectives.